Doing data science - O'Neil, Cathy (O'Reilly, 2014)
Now that people are aware that data can make the difference in an election or a business model, data science as an occupation is gaining ground. But how can you get started working in a wide-ranging, interdisciplinary field that's so clouded in hype? This insightful book tells you what you need to know.